2006
DOI: 10.2459/01.jcm.0000223251.26988.c5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of metalloproteinases-9 and -2 in the acute and subacute phases of type A and type B aortic dissection

Abstract: This pilot study suggests that the acute and subacute phase of both type A and type B aortic dissection is characterized by an increase of MMP-9 plasma levels. A marked increase is also evident in the subacute phase of medically treated type B aortic dissection as an expression of aortic wall remodelling. An increase of proteolytic activity could accompany attempts of the dissected aorta to heal itself but such a phenomena might further weaken the aortic wall, predisposing it to dilation and/or rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 29 publications
1
41
1
7
Order By: Relevance
“…The increase in proteolytic activity that may be responsible for AAD is not necessarily reflected in TIMP expression [19]. Our findings suggest that TIMP-2 was expressed at a low level and MMP-2 at a high level, compatible with the view that the former change favors matrix degradation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The increase in proteolytic activity that may be responsible for AAD is not necessarily reflected in TIMP expression [19]. Our findings suggest that TIMP-2 was expressed at a low level and MMP-2 at a high level, compatible with the view that the former change favors matrix degradation.…”
Section: Discussionsupporting
confidence: 67%
“…Reportedly, increased MMP-9 and MMP-2 expression in macrophages was observed at the site of the intimal tear in 6 patients with atherosclerosis related dissections [12,18]. Several clinical studies have shown an increase in MMP-9 levels in the acute and subacute phase of both type A and B aortic dissection [19,20]. A catabolic action by MMP-9 on elastin proteins may result in weakening of the mechanical properties of the aorta, predisposing it to expansion and/or rupture [21].…”
Section: Discussionmentioning
confidence: 99%
“…Further confirming our results, the expression of MMP-12 has been reported within aortic specimens [9,10] both in humans and in mice [11], and it has been specifically related to the pathogenesis of aneurysms occurring both in ascending and in abdominal aortas [12,13]. This is different from what occurs with MMP-2 and MMP-9, which are released by several immune cells and have been related to matrix remodeling also in atherosclerotic plaque [14,15,16,17]. …”
mentioning
confidence: 44%
“…In particular, the unbalance between MMP-2 and MMP-9/TIMP-1 and TIMP-2 has been extensively reported, with aneurysms and dissections occurring both in thoracic and abdominal aortas [13,14,15,16,17,18]. Moreover, the 4 human TIMPs (1-4) are released by a wide spectrum of circulating and tissue cells [7] and show a considerable overlap in their ability to target different MMPs, so that MMP-2, MMP-9, and MMP-12 share the same TIMP-1 [7,18,19], although some differences in the affinity of specific inhibitor-protease pairs do occur [20,21].…”
mentioning
confidence: 99%
“…Destruction of elastic fibers was also significantly inhibited by transfection of chimeric decoy oligodeoxynucleotide in both hypertensive and normotensive rats [32]. Sangiorgi et al [33] also observed increased MMP-9 in patients with type A or B aortic dissection.…”
Section: Acute Aortic Syndromementioning
confidence: 84%